CORRELATION BETWEEN ANXIETY AND READING COMPREHENSION: A STUDY IN A SECONDARY SCHOOL - Ni Putu Hana Ratna Dewi; I Gde Putu Agus Pramerta (Academic Journal on English Studies (AJOES), 2021)
This study aims to find out the significant correlation between anxiety and reading comprehension of the eighth-grade students in SMPN 2 Mengwi academic year 2020/2021. The research used ex-post facto in form of correlational study. The population of the present study consisted of 337 students and 31 of them were chosen as the samples. They were determined by means of cluster random sampling technique with lottery system. Questionnaire for students’ anxiety and multiple choice test for the students reading comprehension were used as the instruments. The researchers analysed the data through normality test, homogeneity test, Pearson product moment, and t-testing. The result showed the Sig. (2-tailed) was 0.044 and it is lower than 0.05 (0.00 < 0.05). The directional hypothesis in the present study indicated that there is a significant correlation between students’ anxiety and reading comprehension was accepted. It could be concluded that the data had already proven that students’ anxiety was significantly correlated with reading comprehension.